Family business - Howorth, Carole; Robinson, Nick (Routledge masters in entrepreneurship, 2021)
"Family businesses are the most common business form in the world, ranging from the millions of small local businesses to giants such as Walmart. This book showcases the crucial contribution that family businesses make to the world economy, and informs students of the existing and potential research in this area. Drawing upon global academic research and case studies, theories of family businesses are explained and prevailing myths and assumptions are tested. Features including exercises linked to case studies develop skills in applying theories in practice. This concise textbook is essential reading for students of family business and useful additional reading for those interested in entrepreneurship more broadly"--